PENGGUNAAN EKSTRAK KELOPAK JANTUNG PISANG KEPOK (Musa acuminate L.) DALAM FORMULASI PEWARNA RAMBUT - Thaib, Cut Masyithah; Fitri, Raissa; Nurbaya, Siti; Simatupang, Aprili Yanti (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Hair dye preparations are cosmetics used in hair makeup to color hair, either to restore the original hair color or change the original hair color to a new color. Kepok banana heart contains dyes and produces anthocyanins which are used as a safe food coloring. The purpose of this study was to determine that the leaf extract of the Kepok banana heart can be formulated as a hair dye and to determine the concentration of the banana flower extract that produces the best color. Kepok banana flower petals were extracted by maceration method using 96% ethanol, then concentrated to obtain Kepok banana flower petals extract. Hair dye preparations were made with a formula consisting of Kepok banana flower petals extract with various concentrations, namely: 2.5%, 5%, 7.5% and 10%. Staining is done by soaking for 1-4 hours. Observation of color stability was carried out by means of a stability test against 15 washings and exposure to the sun for 5 hours on colored hair, and a biological test (irritation). This study showed that the formula made with the extract of the petals of the Kepok banana heart can give a black color. The best staining was obtained from formula C, namely the extract of the petals of the banana heart of the Kepok banana with a concentration of 7.5% which produced a dark black color. The stability test for 15 washes and the stability test against the sunlight for 5 hours showed that there was no discoloration and no irritation to the skin. It can be concluded that Kepok banana flower petal extract can be used as hair dye.